2018
DOI: 10.3846/ijspm.2018.1416
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing the Rent-to-Price Ratio for the Housing Market at the Micro-Spatial Scale

Abstract: The rent-to-price ratio is one of the popular indicators for monitoring the property market. This study explores micro-scale spatial dynamics of the ratio for houses at the individual property level in Seoul, South Korea. We match the apartment unit sold and the one leased based on the carefully chosen criteria and apply a Bayesian multi-level modeling approach to this matched dataset. We employ the Integrated Nested Laplace Approximations (INLA) algorithm in order to estimate relevant parameters in the multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Exchange rates Lee and Park (2018) South Korea (2016) By using Integrated Nested Laplace Approximation algorithm, the study revealed that at individual property level, interest rates and physical attributes of a dwelling determine the price-to-rent ratio.…”
Section: Cronin and Mcquinn (2016)mentioning
confidence: 99%
See 1 more Smart Citation
“…Exchange rates Lee and Park (2018) South Korea (2016) By using Integrated Nested Laplace Approximation algorithm, the study revealed that at individual property level, interest rates and physical attributes of a dwelling determine the price-to-rent ratio.…”
Section: Cronin and Mcquinn (2016)mentioning
confidence: 99%
“…From a market perspective, whilst research has examined the P-t-R ratio from a life-cycle model of housing tenure choice or present value perspective, there remain relatively limited insights examining the temporal variations of the P-t-R ratio relative to market determinants and fundamental macroeconomic and financial factors. As outlined in Table 1, a number of studies have sought to analyse the role of mortgage/interest rates (Otto, 2007;Tsai and Peng, 2011;Kim and Lim, 2014;Lee and Park, 2018), money supply (Tsai and Peng, 2011), housing supply (Kishor and Morley, 2015), housing investment (Guo and Huang, 2010;Zhai et al, 2018), inflation (Tsai and Peng, 2011), exchange rates (Bahmani-Oskooee and Wu, 2018) and stock market performance (Okunev et al, 2000) vis-a-vis house prices and the P-t-R ratio. Most of these studies have, however, examined the P-t-R dynamics in the context of macroeconomic fundamentals of just one or two particular aspects of the market.…”
Section: Price-to-rent Ratio and Macroeconomic Factorsmentioning
confidence: 99%
“…Fluctuation in housing prices touches the nerves of policymakers, ordinary residents, and financial institutions (Dietzel, 2015) and has become an issue of general social concern. Any imbalance or contraction in the housing market can lead to financial instability, which in turn poses a macroeconomic threat (Lee & Park, 2018). Therefore, how to stabilize the housing market has become a top priority for the development of the real estate industry.…”
Section: Introductionmentioning
confidence: 99%
“…Following the literature on bubble detection [26,27] we focused on the price-to-rent ratios (rather than real price) to control for economic fundamentals. Rent has been shown to be a major indicator of real estate market sustainability [3,12,28]. Comparing six methods for measuring real estate bubbles, Bourassa et al, [27] concluded that the price-to-rent ratio measure is the most reliable method, both ex-post and in real-time, for identifying real estate bubbles.…”
Section: Introductionmentioning
confidence: 99%